By-production of electricity and particulates: efficiency of Indian thermal power plants revisited. Issue 2 (21st August 2021) - Sengupta, Debarun; Mukherjee, Deep
Abstract : Purpose: This paper studies the efficiency of Indian coal-fired thermal power plants (CTPPs) in by-production of electricity and particulates also known as Suspended Particulate Matter (SPM). Design/methodology/approach: A non-radial directional distance function is optimized using data envelopment analysis to enumerate the overall inefficiency of CTPPs and its components in recent times. Further, second-stage regression analysis is conducted to identify factors that affect the inefficiency of plants. Findings: The low inefficiency score for electricity generation suggests that most CTPPs operate close to the good output frontier. A high degree of emissions inefficiency is a challenge for Indian CTPPs. Ever-rising coal use inefficiency is a hindrance to control SPM emissions. The second stage regression analysis concludes that factors like ownership and capacity utilization play vital roles in determining a plant's inefficiency level. Privately owned CTPPs have performed better in terms of technical inefficiency and emission inefficiency than plants owned by Central and State governments. Originality/value: To the best of the authors' knowledge, this study is one of the few published works that benchmark the productive and environmental performance of Indian CTPPs.